PERAN PEMERINTAHAN DESA DALAM MEMBERDAYAKAN MASYARAKAT DESA SINDANGKARYA KECAMATAN MENES KABUPATEN PANDEGLANG - Andriana, Encep (Jurnal Pengabdian Dinamika, 2021)
This socialization activity aims to provide debriefing to village officials and village community institutions to improve living standards and improve the welfare of the community because it is one of the tasks of the government. Community efforts can prosper through community empowerment with the ultimate goal of creating an independent community. Improving the standard of living and the welfare of the community is one ofthe tasks of the government. Efforts to improve the welfare of the community can be carried out through community empowerment with the ultimate goal of creating an independent society. In carrying out community empowerment, it is necessary to involve other parties, one of which is village community institutions. In carrying out community development, it is necessary to involve other parties, one of which is village community institutions. The method used during the implementation of this service is the method of direct counseling or socialization to the administrators or local village officials. Based on the results of the socialization, the authors conclude that normatively the relationship between Community Institutions and the Village Government is to become a partnership as regulated in the legislation.